Предмет: Математика,
автор: lagutkinapolina2007
Зx(4x-1) - 2х( 4x+5)
1) Упростите выражение
Ответы
Автор ответа:
1
Ответ: 4x²-13x = x(4x-13).
Пошаговое объяснение:
Упростите выражение
Зx(4x-1) - 2х( 4x+5)=12x²-3x-8x²-10x=4x²-13x = x(4x-13).
lagutkinapolina2007:
а разве не 4х^2+7?
Похожие вопросы
Предмет: Другие предметы,
автор: сима64
Предмет: Английский язык,
автор: дара8
Предмет: Русский язык,
автор: SeaAndWater
Предмет: Русский язык,
автор: rabkovich1975
Предмет: Математика,
автор: новичёк337